Production of bioactive peptides from striped catfish (Pangasius hypophthalmus) skin by enzymatic membrane reactor - Hue Quoe Hoa (Prince of Songkla University, 2015)
Thesis (M.Sc. (Functional Food and Nutrition))--Prince of Songkla University, 2014